Respon Fisiologis dan Produksi Rimpang Kunyit Hitam (Curcuma Caesia Roxb) Terhadap Aplikasi Pupuk Organik Cair Daun Kelor (Moringa Oleifera) dan Kulit Pisang: Penelitian - Ikbal Maulana; Muhammad Aksan; Firman; Muhammad Faisal (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of liquid organic fertilizer (POC) application made from Moringa oleifera leaves and banana peels on the physiological response and production of black turmeric (Curcuma caesia Roxb) rhizomes. Black turmeric is a herbal plant with high economic value, but its productivity in Indonesia is still low due to limited cultivation techniques and dependence on chemical fertilizers. The study was conducted at the TAPOJI Green House, Muhammadiyah University of Sidenreng Rappang, using a Randomized Block Design (RAK) with seven POC dose treatments (0%, 5%, 10%, 15%, 20%, 25%, and 30%) and three replications, resulting in 84 experimental units. The parameters observed included plant height, number of leaves, stem diameter, leaf color, fresh weight of rhizomes, and number of rhizomes per plant. The results showed that the application of POC significantly affected several parameters of vegetative growth and production of black turmeric rhizomes. Medium concentration treatments, particularly 10–20%, provided the best physiological response, resulting in increased plant height, leaf number, and stem diameter, while also producing higher rhizome fresh weight and rhizome number per plant compared to the control. Conversely, high concentrations (25–30%) tended to decrease plant performance due to excess nutrients.